Clinical and organizational applications of applied behavior analysis - Roane, Henry S.; Ringdahl, Joel E.; Falcomata, Terry S. (Amsterdam : Academic Press : Elsevier, 2015)
Clinical and Organizational Applications of Applied Behavior Analysis uses data-based decision making to inform treatment selection for behavior change across various populations and contexts. Each chapter addresses considerations related to data collection, single-case research design methodology, objective decision-making, and visual inspection of data. Not only do the authors draw on a range of published research methods in the area of Applied Behavior Analysis (ABA) as it has been applied to a specific topic, but they also draw upon their own clinical work by providing case examples. Comp.
Increasing Acceptance and Decreasing Inappropriate Mealtime BehaviorEscape Extinction; Positive Reinforcement; High-Probability Instructional Sequence; Simultaneous Presentation; Stimulus Fading; Decreasing Expulsion and Packing; Re-presentation; Chin Prompt; Presentation Manipulations; Texture Reduction; Redistribution; Chaser; Caregiver Training; Conclusion; References; Chapter 5: ABA Applications in the Prevention and Treatment of Medical Problems; Introduction; Pediatric Neurology-Recurrent Headaches; Prevalence and Significance; Etiology; Behavioral Interventions.
Online resource; title from PDF title page (EBSCO, viewed June 26, 2015).
Includes bibliographical references and index.
Keywords: Behaviorism (Psychology); Human behavior; PSYCHOLOGY -- Reference; Behaviorism (Psychology); Human behavior; Behavior Therapy; Evidence-Based Medicine; Mental Disorders -- therapy; Electronic books; Electronic books